Sensitivity And Specificity Numerical Range Scale-Competency (NRS-C) In Emergency Care - Heru Suwardianto; Santi Angraini (Poltekkes Kemenkes Surakarta, 2021)
Background: Emergency conditions always occur every day around us, and the delay in aid makes the condition getting worse after arriving at the emergency department. Emergency competency assessments that continue to develop ensure increased competence for students to further increase student awareness of emergency conditions. The research objective is the development of the Emergency Sensitivity and Specificity Range Scale Competency (NRS-C) for Emergency Services Methods: Observational analytical research method using secondary data competency assessment of 101 respondents who have done daily emergency training. Inclusion criteria, namely high school students’ class XI and XII. The sampling technique used is random sampling by taking randomly (single blink). Data were analyzed using the Receiver Operating Curve (ROC Curve). Results: The results showed that most respondents were 16 years old (41%), and have a female gender (54%). The results showed that the sensitivity value was 84% and the specificity was 16%, with an AUC Area value of 0.794, and p=0,001, which means it has a fairly good AUC value. Conclusion: The NRS-C instrument can be used in the emergency department competency assessment which is quite good in assessing the competence of an emergency department..